Wafer-scale epitaxial lift-off of optoelectronic grade GaN from a GaN substrate using a sacrificial ZnO interlayer. (15th July 2016) - Rajan, Akhil; Rogers, David J; Ton-That, Cuong; Zhu, Liangchen; Phillips, Matthew R; Sundaram, Suresh; Gautier, Simon; Moudakir, Tarik; El-Gmili, Youssef; Ougazzaden, Abdallah; Sandana, Vinod E; Teherani, Ferechteh H; et al.
Abstract: Full 2 inch GaN epilayers were lifted off GaN and c-sapphire substrates by preferential chemical dissolution of sacrificial ZnO underlayers. Modification of the standard epitaxial lift-off (ELO) process by supporting the wax host with a glass substrate proved key in enabling full wafer scale-up. Scanning electron microscopy and x-ray diffraction confirmed that intact epitaxial GaN had been transferred to the glass host. Depth-resolved cathodoluminescence (CL) analysis of the bottom surface of the lifted-off GaN layer revealed strong near-band-edge (3.33 eV) emission indicating a superior optical quality for the GaN which was lifted off the GaN substrate. This modified ELO approach demonstrates that previous theories proposing that wax host curling was necessary to keep the ELO etch channel open do not apply to the GaN/ZnO system. The unprecedented full wafer transfer of epitaxial GaN to an alternative support by ELO offers the perspective of accelerating industrial adoption of the expensive GaN substrate through cost-reducing recycling.